Does increased access to health insurance impact claims for workers' compensation? Evidence from Massachusetts health care reform - Erin Todd Bronchetti; Melissa McInerney (W.E. Upjohn Institute for Employment Research, 2017)
We study over 20 million emergency room (ER) discharges in Massachusetts and three comparison states to estimate the impact of Massachusetts health care reform on claims for Workers' Compensation (WC). Prior evidence on the relationship between health insurance and WC claiming behavior is mixed. We find that the reform caused a significant decrease in the number of per-capita ER discharges billed to WC. This result is driven by larger decreases in WC discharges for conditions for which there is greater scope to change the payer or the location of care. Conversely, we estimate smaller impacts for weekend versus weekday admissions and for wounds compared to musculoskeletal injuries. Our findings are consistent with the reform lowering WC medical costs for employers/insurers, primarily by inducing injured workers to seek care at less costly sites. The results suggest much smaller impacts on the propensity to bill WC for a given injury.
Keywords: I11; I13; J32; 330; Workers' compensation; health insurance; claiming behavior